The effectiveness of lavender aromatherapy in managing labor pain - Muna, Sirajul; Wahyuni, Sri (Institute of Computer Science (IOCS), 2025)
Labor pain is one of the most intense forms of acute pain experienced by women and can have significant physical and psychological impacts. Although pharmacological methods such as epidural anesthesia are effective in relieving pain, their use is associated with potential side effects and limitations in resources, particularly in healthcare facilities with restricted access. This study aims to evaluate the effectiveness of lavender aromatherapy in managing labor pain, as well as to review the methods of application, timing of administration, and associated psychological effects based on empirical evidence from various studies. This literature review analyzed 17 scientific articles employing various research designs, including randomized controlled trials (RCTs), quasi-experimental studies, comparative studies, and systematic reviews. Data sources were derived from both national and international journals relevant to the topic of lavender aromatherapy and labor pain. The findings indicate that lavender aromatherapy consistently reduces labor pain intensity, particularly when applied during the active phase of the first stage of labor. Additionally, it has anxiolytic effects that help alleviate maternal anxiety. Its combination with other techniques such as effleurage massage enhances analgesic efficacy by stimulating beta-endorphin production. Lavender aromatherapy also offers flexibility in its application methods, including inhalation, topical massage, and ambient diffusion. Lavender aromatherapy is a safe, effective, and easily implemented non-pharmacological approach to holistic labor pain management. It supports both the physical and emotional well-being of mothers throughout the childbirth process.